Application of Kegel Gymnastics in Reducing Urinary Incontinence in the Elderly in Gampong Lamleuot, Kuta Cot Glie District, Aceh Besar - Rahmiati, Cut; Afrianti, Novi (International Journal Labs, 2023)
The elderly are someone who has reached the age of 60 years and over, where in old age a person has experienced various declines in system function, as well as changes in body structure, one of which is a change in the structure of the urinary system and has weakened pelvic floor muscles and decreased bladder capacity, so the elderly are very vulnerable to urinary incontinence. Urinary incontinence is a bladder sphincter defect or neurological dysfunction that causes loss of control over urination. Thus causing a person to experience physical, psychological, social, and economic problems that affect the quality of life of the elderly, one of the treatments for urinary incontinence in the elderly is by practicing Kegel exercises. The purpose of this study was to find out the picture of the application of Kegel exercises in reducing urinary incontinence in the elderly with urinary incontinence. This research method is a case study with 2 (two) research subjects, which was carried out in Gampong Lamleuot, Kuta Cot Glie District, Aceh Besar Regency on March 9-20, 2023. The instruments used are SOPs for Kegel exercises, observation sheets and Resived Urinary Incontinence Scale (RUIS) questionnaires. The results showed a decrease in the level of incontinence in the elderly after the application of Kegel exercises, thus it is hoped that elderly gymnastics can be used as one of the therapies in reducing the level of urinary incontinence in the elderly.